2009
DOI: 10.1080/08870440902883212
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial and behavioural contributors to health: Age-related increases in physical disability are reduced by physical fitness

Abstract: The aging process is associated with increased risk for disease which can cause physical and economic burden for older adults. In a national longitudinal sample of 3910 participants aged 24-75 years (55% women), we examined psychosocial and behavioural factors associated with physical health in adulthood. With hierarchical regression analyses controlling for Time 1 values of the dependent variable and demographic characteristics, we found that participants reporting better social relations, a higher sense of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 38 publications
2
26
0
Order By: Relevance
“…Nevertheless, our results were generally consistent when individuals with serious morbidities at recruitment were analysed. We used only baseline SRH which may have changed during follow-up, although SRH is considered to remain stable even after major health events [41].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, our results were generally consistent when individuals with serious morbidities at recruitment were analysed. We used only baseline SRH which may have changed during follow-up, although SRH is considered to remain stable even after major health events [41].…”
Section: Discussionmentioning
confidence: 99%
“…Because healthier individuals tend to be more active,39 we controlled for current self-rated health. Self-rated health was measured with 1 item asking participants to rate, on a 5-point scale, “In general, would you say your physical health is excellent (5), very good (4), good (3), fair (2), or poor (1)?” Responses ranged from 1 to 5 (mean = 3.57, SD = 1.00).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, high life engagement appeared to serve as a protective resource, thereby reducing the risk of future disability and mortality for these individuals. A related study from MIDUS (Cotter & Lachman, 2010) found that physical health decline with aging was significantly reduced among those with positive profiles on three protective factors (control beliefs, social support, physical exercise).…”
Section: Empirical Examples Of Resilience and Their Relevance For Healthmentioning
confidence: 99%